Entrepreneurship and the Extensive Margin in Export Growth : A Microeconomic Accounting of Costa Rica’s Export Growth during 1997-2007 - Lederman, Daniel; Rodríguez-Clare, Andrés; Yi Xu, Daniel (World Bank, 2013)
Successful exporting countries are often seen as successful economies. This paper studies the role of new exporting entrepreneurs – defined as firms that became exporters – in determining export growth in a fast growing and export oriented middle-income country i.e., Costa Rica during 1997-2007. It provides a detailed description of the contribution of export entrepreneurs in the short and long run, and comparing the observed patterns with an emerging literature on the role of the “extensive” margin in international trade. On a year-by-year basis, the rate of firm turnover into and out of exporting is high, but exit rates decline rapidly with age (i.e., the number of years the firm has been exporting). On average, about 30 percent of firms in each year tend to exit export activities, and a similar percentage of firms enter. The exiting and entering firms tend to be significantly smaller than incumbent firms in terms of export value (e.g., entrants export about 30 percent less on average than incumbent firms). These findings are consistent with existing evidence for other middle income Latin American countries. However, in the long run new product-firm combinations (i.e., product-firm combinations not present in 1997) account for almost 60 percent of the value of exports in 2007. Surviving new exporters actively adopted new products (for the firm, but not necessarily new for the country) and abandoned weaker existing products they start with, and their export growth rates were very high during a period (1999-2005) when those of incumbent exporting firms were actually negative.